"Everything feels risky now": Perceived "risky" sexual behavior during COVID-19 pandemic. (May 2022) - Bowling, Jessamyn; Montanaro, Erika; Gattuso, Jennifer; Gioia, Diana; Guerrero Ordonez, Sarai
Social distancing through the COVID-19 pandemic has impacted sexuality and relationships, which may also change risk perceptions beyond traditional definitions (e.g. sexually transmitted infections). This study examines risk perceptions related to sexuality during the pandemic. We present qualitative analyses of a survey of adults in the United States ( N = 333) to identify impacts of COVID-19 on individuals' risk perceptions. Risky sexual behavior definitions included: (1) COVID-19-related, (2) STI/pregnancy, (3) relationship-related, (4) physical boundaries, (5) drug or alcohol, and (6) multiple risks. Conventional public health messaging may need to incorporate changing risk definitions to address sexual health during the pandemic.